FACIES AND PETROGRAPHIC CHARACTERISTICS OF CILETUH FORMATION IN THE MANDRAJAYA AREA, CIEMAS SUBDISTRICT, WEST JAVA - Sayaf, Ival Umar; Isnaniawardhani, Vijaya; Hardiyono, Adi; Natasia, Nanda (Bulletin of Scientific Contribution, 2025)
The Eocene Ciletuh Formation, exposed within the Ciletuh-Palabuhanratu UNESCO Global Geopark, provides a key record of syn-tectonic sedimentation in West Java. While its general submarine fan setting is known, detailed facies and petrographic studies in specific localities are limited. This study aims to characterize the sedimentology of the Ciletuh Formation sandstone in the Mandrajaya area through an integrated analysis of lithofacies, petrography, and their spatial distribution to reconstruct its depositional environment. The methodology involved geological mapping to document outcrop characteristics and collect samples, followed by petrographic analysis of sandstones and conglomerates. Four primary lithofacies were identified: (a) matrix-supported polymictic conglomerate, (b) graded sandstone, (c) parallel-laminated sandstone, and (d) massive sandstone. Petrographic analysis reveals that the sandstones are texturally immature Lithic Arenites, and the conglomerates contain polymictic clasts of gabbro and recycled sandstone within a similar lithic arenite matrix. The spatial distribution of these facies delineates a submarine fan architecture, characterized by channel-fill deposits (conglomerates and massive sandstones) flanked by associated levee and overbank deposits (graded and laminated sandstones). The lithofacies association and petrographic composition confirm deposition within a dynamic submarine fan system sourced from a "Recycled Orogenic" belt, specifically the uplifted Ciletuh mé‎lange complex, within a tectonically active Paleogene fore-arc basin.Keywords: Submarine Fan, Lithic Arenite, Conglomerate, Fore-arc Basin, Sedimentation, Turbidite, Eocene.